Hybridizing MWCNT with nano metal oxides and TiO2 in epoxy composites: Influence on mechanical and thermal performances. Issue 34 (11th May 2016) - Gazderazi, Masoomeh; Jamshidi, Masoud
ABSTRACT: In this study, the effects of multi‐walled carbon nanotubes (MWCNT), and its hybrids with iron oxide (Fe2 O3 ) and copper oxide (CuO) nanoparticles on mechanical characteristics and thermal properties of epoxy binder was evaluated. Furthermore, simultaneous effects of using MWCNT with TiO2 as pigment and CaCO3 as filler for epoxy composites were determined. To investigate effects of nano‐ and micro‐particles on epoxy matrix, the samples were evaluated by TGA and DTA. It was found that the hybrid of MWCNT with nano metal oxides caused considerable increment in the tensile and flexural properties of epoxy samples in comparison to the single MWCNT containing samples at the same filler contents. Significant improvement in the thermal conductivity of epoxy samples was obtained by using TiO2 pigment along with MWCNT. The TiO2 pigment also caused considerable improvement in mechanical properties of the epoxy matrix and the MWCNT containing nanocomposite. The best mechanical and thermal properties of epoxy nanocomposites were obtained at 1.5 wt % of MWCNT and 7 wt % of TiO2 that it should be attributed to particle network forming of the particles which cause better nano/micro dispersion and properties. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43834. Abstract :